Pelatihan Manajemen Pemasaran Guna Membangun Jejaring Pemasaran di Masa Pandemi Pada Konveksi Angkola Jaya Tapanuli Selatan - Azhar, Intan Nisa (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Covid 19 has had a considerable impact on various sectors in Indonesia, especially the convection business sector. Konvection Ankola Jaya in South Tapanuli Regency in facing internal and external problems so that convection has not been able to make an optimal contribution like other economic businesses or institutions. One of the problems is the limitations of the Angkola Jaya Convection in accessing information and market coverage, labor networks, and access to strategic locations for businesses during the Covid 19 Pandemic. The goal to be achieved is to improve the performance of Angkola Jaya Covection in South Tapanuli Regency with the presence of network convection. The specific target to be achieved is to improve the performance of the Angkola Jaya Convection in South Tapanuli Regency by implementing marketing management. The importance of services is expected to improve the performance of the Angkola Jaya Convection through learning exploration of human resources, encouraging efficient use of resources, increasing planning and implementation capacity to solve problems, increasing networking, with business partners and increasing competitiveness, providing better services. both to clients and customers